Planetary science and exploration in the deep subsurface: results from the MINAR Program, Boulby Mine, UK - Payler, Samuel J.; Biddle, Jennifer F.; Coates, Andrew J.; Cousins, Claire R.; Cross, Rachel E.; Cullen, David C.; Downs, Michael T.; Direito, Susana O. L.; Edwards, Thomas; Gray, Amber L.; Genis, Jac; Gunn, Matthew; et al. (Cranfield University, 2016)
The subsurface exploration of other planetary bodies can be used to unravel their geological history and assess their habitability. On Mars in particular, present-day habitable conditions may be restricted to the subsurface. Using a deep subsurface mine, we carried out a program of extraterrestrial analog research – MINAR (MINe Analog Research). MINAR aims to carry out the scientific study of the deep subsurface and test instrumentation designed for planetary surface exploration by investigating deep subsurface geology, whilst establishing the potential this technology has to be transferred into the mining industry. An integrated multi-instrument suite was used to investigate samples of representative evaporite minerals from a subsurface Permian evaporite sequence, in particular to assess mineral and elemental variations which provide small scale regions of enhanced habitability. The instruments used were the Panoramic Camera emulator (AUPE-2), Close-Up Imager (CLUPI), Raman Spectrometer, SPLIT (Small Planetary Linear Impulse Tool), Ultrasonic Drill and handheld XRD. We present science results from the analog research and show that these instruments can be used to investigate in situ the geological context and mineralogical variations of a deep subsurface environment, and thus habitability, from millimeter to meter scales. We also show that these instruments are complementary. For example, the identification of primary evaporite minerals such as NaCl and KCl, which are difficult to detect by portable Raman spectrometers, can be accomplished with XRD. By contrast, Raman is highly effective at locating and detecting mineral inclusions in primary evaporite minerals. MINAR demonstrates the effective use of a deep subsurface environment for planetary instrument development, understanding the habitability of extreme deep subsurface environments on Earth and other planetary bodies, and advancing the use of space technology in economic mining.